1999
DOI: 10.1073/pnas.96.23.13180
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc enhances protein synthesis and cell size during B lymphocyte development

Abstract: It has been known for some time that cell cycle progression is tightly coupled to an accumulation of cell mass (i.e., cell growth) (1). However, the molecules that control cell growth and the mechanisms through which growth and proliferation are coupled are only beginning to be defined (2). One group of genes whose function may be important for both growth and proliferation is the members of the myc protooncogene family, c-, N-, and L-myc.The proteins encoded by myc family genes are members of the basic-helix-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
225
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(254 citation statements)
references
References 55 publications
25
225
0
4
Order By: Relevance
“…In addition, it is intriguing that bone marrow pre-B cells appeared more resistant to inhibition of glycolysis than their more mature IgM + progeny (45). In any case, the emergence of lymphoma is thought to be due in part to the accumulation of an expanded pre-B population in Eμ-myc mice (27,28). Thus, the combined changes may account for the contribution of this BAL-family ADP ribosyltransferase to Mycinduced lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is intriguing that bone marrow pre-B cells appeared more resistant to inhibition of glycolysis than their more mature IgM + progeny (45). In any case, the emergence of lymphoma is thought to be due in part to the accumulation of an expanded pre-B population in Eμ-myc mice (27,28). Thus, the combined changes may account for the contribution of this BAL-family ADP ribosyltransferase to Mycinduced lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we found that PARP14 is crucial for Eμ-myc cells fully to increase their glycolysis and size. Thus, the proliferative drive and faster protein synthesis forced by sustained c-Myc overexpression (27,28) must contend with a restriction on the rate of glycolysis when PARP14 is absent. Rapid engulfment of apoptotic cells in vivo precludes accurately measuring rates of apoptosis in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the opposite, downregulation of c-myc expression in A549 cells retarded cell growth and caused G1 phase arrest. cmyc enhances cell size during B lymphocyte development and can enhances cell growth to levels required for unrestrained cell division (Iritani and Eisenman, 1999). c-myc is involved in the regulation of cell growth via increase cell size (Johnston et al, 1999;Schuhmacher et al, 1999), but could not override a size control on S phase entry (Neufeld and Edgar, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Myc overexpression leads to reduced requirements for growth factors, blocks exit from cell cycle, and accelerates cell division. (12)(13)(14) Myc levels diminish during terminal differentiation of many cell types and its overexpression inhibits differentiation. However, recent data suggest that Myc also may play a role in moving cells along during hematopoietic and epidermal differentiation.…”
Section: Introductionmentioning
confidence: 99%